Agmatine has beneficial effect on harmaline-induced essential tremor in rat - ARICIOĞLU, FEYZA (ELSEVIER IRELAND LTD, 2021)
Essential tremor (ET) is one of the most prevalent movement disorders and the most common cause of abnormal tremors. However, it cannot be treated efficiently with the currently available pharmacotherapy options. The pathophysiology of harmaline-induced tremor, most commonly used model of ET, involves various neurotransmitter systems including glutamate as well as ion channels. Agmatine, an endogenous neuromodulator, interacts with various glutamate receptor subtypes and ion channels, which have been associated with its? beneficial effects on several neurological disorders. The current study aims to assess the effect of agmatine on the harmaline model of ET. Two separate groups of male rats were injected either with saline or agmatine (40 mg/ kg) 30 min prior to single intraperitoneal injection of harmaline (20 mg/kg). The percent duration, intensity and frequency of tremor and locomotor activity were evaluated by a custom-built tremor and locomotion analysis system. Pretreatment with agmatine reduced the percent tremor duration and intensity of tremor induced by harmaline, without affecting the tremor frequency. However, it did not affect the decreased spontaneous locomotor activity due to harmaline. This pattern of ameliorating effects of agmatine on harmaline-induced tremor provide the first evidence for being considered as a treatment option for ET.
Keywords: Harmaline; Essential tremor; Agmatine; Rat; INDUCED SEIZURES; POSTURAL TREMOR; CALCIUM-CHANNEL; INDUCED MODEL; INHIBITION; NEURONS